Microwave-hydrothermal synthesis of extremely high specific surface area anatase for decomposing NO x - Sonthikan Sitthisang (2018)
Apparently C-doped and undoped or pure nanoparticles of anatase were synthesized using a microwave hydrothermal process in the temperature range of 140-180 °C for 1 h from several Ti precursors, such as Ti ethoxide, Ti isopropoxide and Ti oxysulfate. Nanoparticles of anatase samples were characterized by powder X-ray diffraction, transmission electron microscopy (TEM) and photocatalytic activity measurements. Results showed that nanoparticles in the size range of 4-17 nm of anatase were obtained in all cases with surface areas in the range of 151-267 m 2 /g. The photocatalytic activity of the prepared titanias was measured using methylene blue (MB) and NO x molecules. Because MB has very strong adsorption on the samples, photocatalytic degradation under either solar light or black light irradiation was found to be very limited. However, the DeNO x abilities of carbon-doped titanias were higher than those of Degussa P25 commercial titania sample and undoped or pure titanias especially under irradiation by long wavelength or visible light ( > 500 nm). © 2012 Elsevier Ltd and Techna Group S.r.l.